Current status and future prospects for the development of substance abuse vaccines - R. David Heekin; Daryl Shorter; Thomas R. Kosten (Taylor & Francis Group, 2017)
Introduction: Substance use disorders (SUD) are a significant threat to both individual and public health. To date, SUD pharmacotherapy has focused primarily on agonist medications (i.e. nicotine replacement therapy for tobacco use disorder; methadone and buprenorphine for opioid use disorder), antagonist medications (i.e. naltrexone for opioid use disorder), and aversive therapy (i.e. disulfiram for alcohol use disorder). Pharmacotherapeutic approaches utilizing an immunological framework for medication development represent an important focus of study for treatment of these illnesses. Areas covered: This review discusses vaccines for treatment of substance use disorders. Using PubMed (https://www.ncbi.nlm.nih.gov/pubmed/), we searched both preclinical and human clinical trials of vaccines for treatment of nicotine, cocaine, methamphetamine, and opioid use disorders. In addition, we searched for recently developed strategies for enhancement of the immunologic response through alteration of conjugate molecules and adjuvants. Expert commentary: Despite challenges in human clinical trials of SUD vaccines, a number of strategies have been introduced which may ultimately improve efficacy. These challenges, as well as their implications for vaccine development, are discussed. Additionally, the optimal conditions for research study and treatment are considered.